Endosome rupture enables enteroviruses from the family Picornaviridae to infect cells - Aygul Ishemgulova; Liya Mukhamedova; Zuzana Trebichalská; Veronika Rájecká; Pavel Payne; Lenka Šmerdová; Jana Moravcová; Dominik Hrebík; David Buchta; Karel Škubník; Tibor Füzik; Štěpánka Vaňáčová; et al. (Communications Biology)
Abstract Membrane penetration by non-enveloped viruses is diverse and generally not well understood. Enteroviruses, one of the largest groups of non-enveloped viruses, cause diseases ranging from the common cold to life-threatening encephalitis. Enteroviruses enter cells by receptor-mediated endocytosis. However, how enterovirus particles or RNA genomes cross the endosome membrane into the cytoplasm remains unknown. Here we used cryo-electron tomography of infected cells to show that endosomes containing enteroviruses deform, rupture, and release the virus particles into the cytoplasm. Blocking endosome acidification with bafilomycin A1 reduced the number of particles that released their genomes, but did not prevent them from reaching the cytoplasm. Inhibiting post-endocytic membrane remodeling with wiskostatin promoted abortive enterovirus genome release in endosomes. The rupture of endosomes also occurs in control cells and after the endocytosis of very low-density lipoprotein. In summary, our results show that cellular membrane remodeling disrupts enterovirus-containing endosomes and thus releases the virus particles into the cytoplasm to initiate infection. Since the studied enteroviruses employ different receptors for cell entry but are delivered into the cytoplasm by cell-mediated endosome disruption, it is likely that most if not all enteroviruses, and probably numerous other viruses from the family Picornaviridae, can utilize endosome rupture to infect cells.